Valorization of Onion Waste by Obtaining Extracts Rich in Phenolic Compounds and Feasibility of Its Therapeutic Use on Colon Cancer - Mónica Paesa; Danielle Pires Nogueira; Gustavo Velderrain-Rodríguez; Irene Esparza; Nerea Jiménez-Moreno; Gracia Mendoza; Jesús Osada; Olga Martin-Belloso; María Jesús Rodríguez-Yoldi; Carmen Ancín-Azpilicueta (MDPI AG, 2022)
In this study, the total phenolic content, the antioxidant and antiproliferative activities of onion waste extracts were characterized. Some phenolic compounds present in the extracts were also identified and quantified by HPLC-DAD. Additionally, an in-silico analysis was performed to identify the phenolic compounds with the highest intestinal absorption and Caco-2 permeability. The onion extract possessed a high amount of phenolic compounds (177 ± 9 mg/g extract) and had an effective antioxidant capacity measured by ABTS, FRAP and DPPH assays. Regarding the antiproliferative activity, the onion extracts produced cell cycle arrest in the S phase with p53 activation, intrinsic apoptosis (mitochondrial membrane potential modification) and caspase 3 activation. Likewise, onion waste increased intracellular ROS with possible NF-kB activation causing a proteasome down regulation. In addition, the extracts protected the intestine against oxidative stress induced by H2O2. According to the in-silico analysis, these results could be related to the higher Caco-2 permeability to protocatechuic acid. Therefore, this study provides new insights regarding the potential use of these types of extract as functional ingredients with antioxidant and antiproliferative properties and as medicinal agents in diseases related to oxidative stress, such as cancer. In addition, its valorization would contribute to the circular economy.